Penatalaksanaan Pencabutan Gigi pada Pasien Hipertiroid - Dian Yosi Arinawati; Asyam Syafiq Allam; Romadhon Yuan Aziz (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Hyperthyroidism is a condition in which thyroid hormones are overproduced. Medications used in oral care can cause reactions in patients with thyroid disorders and should be considered before treatment. Invasive treatment at the dentist requires a good systemic and mental state of the patient. So that patients avoid post-treatment complications that can be dangerous. The purpose of this case report is to determine the treatment plan for tooth extraction in a patient with hyperthyroidismA woman came to the Dental and Oral Hospital (RSGM) with complaints of discomfort when eating because of the remaining tooth roots. The previous mandibular tooth had been extracted 15 years ago. The patient had a history of hyperthyroidism and was currently taking routine medication for her hyperthyroidism. Treatment will be carried out to the patient in the form of extraction, conditioning the patient (taking medication, resting, and eating) before extraction. Post extraction medication is amoxicillin and ibuprofen. Preparation to handle complications that may occur, such as knowledge about emergencies and preparation of oxygen cylinders. The patient's condition can worsen at any time so it is necessary to prepare the nearest emergency room contact. Dentists need to recognize the clinical symptoms of hyperthyroid conditions. Dentists also need to take an in-depth history of the patient's systemic condition, so that complications due to improper treatment of patients can be avoided.